Perbedaan Persepsi dan Harapan Wisatawan Lokal dengan Wisatawan Asing terhadap Kualitas Layanan di Candi Borobudur - Saputra, Arif Dwi; Susilawati, Heni; Hermawan, Hary (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2019)
Efforts to increase foreign tourists related to tourist attraction need to be interpreted through the attitude of foreign tourists in their perception and expectations of service quality, so that it becomes a more measurable central point when wanting to boost foreign exchange through the tourism service sector. The research that has been done is explorative research with the descriptive quantitative method. The results showed that there were differences in perception and experience of service quality in Borobudur Temple in both groups of tourists